Organizational level antecedents of value co-destruction in hospitality industry: an investigation of the moderating role of employee attribution - Ukeje, Uchechukwu Edwin; Lasisi, Taiwo Temitope; Eluwole, Kayode Kolawole; Titov, Eneken; Ozturen, Ali (Routledge Journals, Taylor & Francis Ltd, 2021)
The recent upsurge in theoretical advances in value co-creation in service organizations provides the credo to uncover the likely predictors of value co-destruction which may sometimes be the end point of the co-creation process. Thus, this paper aims to investigate how hotel employees' perception of leadership support, supportive organizational climate and management's commitment to value co-creation predicts value co-destruction in their organization. The survey was designed to solicit data that will help in answering our main research question; what organizational level factors are responsible for mitigating the deleterious effect of value co-destruction in hospitality industry? In total, 475 hotel employees from sub-Saharan Africa (Nigeria) were surveyed to gather data that was subjected to SEM analysis. The findings confirm leadership support, supportive climate and management's commitment as predictors of value co-destruction while employee attribution only moderates the relationship between management's commitment to value co-creation and value co-destruction. This study unearths the importance of organizational involvement in militating against value co-destruction. Within the specific context of hoteling, management's commitment to value co-creation is moderated by employee attribution style. Practical implications with industry focused best practices are recommended.
Keywords: Value co-creation; value co-destruction; hospitality industry; employee attribution; leadership support; Nigeria & x200c